Conservative surgical treatment of multiple fractures of the face after a fall (Research, Society and Development, 2022)
Facial fractures are a public health problem due to the need for specialized care, adequate environment and financial resources. They have different causes, and sports, work, traffic accidents and falls stand out as the main ones, being the same related to age, gender of the patient and direction of the trauma. This paper aims to report the clinical case of a male patient who fell 4.5 meters high, pushing his face against the edges of a swimming pool. Attended at the Maria Aparecida Pedrossian University Hospital, requiring outpatient and surgical care for the treatment of multiple facial fractures. The initial physical examination showed edema in the middle and lower thirds of the face, preserved visual acuity and ocular motility, mobility in the parasymphysis, laceration in the lower lip, marked mobility in dental elements, fragments of exposed oral bone tissue in the premaxilla region, absence of altered teeth and mandibular movements. Computed tomography showed a comminuted fracture in the anterior maxilla, bilateral fracture of the condyle and fracture of the mandibular parasymphysis on the left side. Thus, the treatment of choice was surgery under general anesthesia for placement of the Erich bar and maxillomandibular block, reduction and fixation of anterior mandible fractures and removal of bone fragments and unsupported teeth in the maxillary region. In the postoperative controls, the patient remained without complaints after the blockage was removed, with preserved mandibular movements and return to masticatory functions. Six months after the trauma, the patient is fully rehabilitated.